The use of electron accelerators for simulation of radiation damage in rock salt considered for safe storage of nuclear waste - Dubinko, V.I.; Dovbnya, A.N.; Borisenko, V.N.; Petrusenko, Yu.T.; Grytsyna, V.M.; Sugonyako, A.V.; Vainshtein, D.I.; den Hartog, H.W. (Вопросы атомной науки и техники, 2006)
Rock salt is one of the considered storage mediums for nuclear high level waste (HLW), and so the behavior of
rock salt in the vicinity of HLW is of great practical interest. The main contribution to the irradiation from a radioactive
waste comes from gamma-radiation, which requires a comparison of its action with that of the electron irradiation,
widely used for simulation of radiation damage in rock salt. To solve this problem, we have used a linear electron
accelerator to produce bremsstrahlung gamma-radiation spectrum similar to the real spectrum of HLW. Samples
of synthetic crystals of NaCl have been γ- irradiated up to the dose ranging from 1.2 10⁸ Gy to 7.8 10⁸ Gy and
subsequently investigated by means of differential scanning calorimetry and atomic force microscopy. Electron and
gamma irradiated samples have shown a comparable damage concentration and the structure of the radiolytic products,
which justifies the use of electron irradiation for the imitation of radiation damage in the vicinity of HLW. Одна из проблем имитации действия радиоактивных отходов (РАО) на среду захоронения заключается в том, что основной составляющей радиационного фона вокруг РАО является гамма-облучение, что требует сравнения его действия с действием имитационного электронного облучения. Для решения этой проблемы было использовано тормозное гамма-излучение, получаемое на линейном электронном ускорителе, близкое по спектру к гамма-излучению РАО. Образцы NaCl были подвергнуты гамма-облучению до доз в интервале 1.2 10⁸…7.8 10⁸ Грей и затем исследованы методом дифференциальной сканирующей калориметрии и атомно-полевой микроскопии. Исследование показало, что концентрация и структура продуктов радиолиза в образцах, облученных гамма-квантами и электронами, хорошо согласуются. Одна із проблем імітації дії радіоактивних відходів (РАВ) на середовище поховання полягає в тім, що
основної складової опромінення навколо РАВ є гамма-опромінення, що вимагає порівняння його дії з дією
імітаційного електронного опромінення. Для вирішення цієї проблеми було використано гальмове гамма-
випромінювання, одержуване на лінійному електронному прискорювачі, що близьке по спектру до гамма-
випромінювання РАВ. Зразки NaCl були піддані гамма-опроміненню до доз в інтервалі 1.2 10⁸ …7.8 10⁸ Грей і потім досліджені методом диференціальної скануючої калориметрії і атомно-польовій мікроскопії. Дослідження показало, що концентрація й структура продуктів радіолізу в зразках, опромінених гамма- квантами і електронами, добре погоджуються.